Чернігівський Борисоглібський собор у 20-30-ті роки XX століття - Рига, Д. (Сiверянський лiтопис, 2016)
У статті йдеться про Чернігівський Борисоглібський собор у 20-30-ті роки XX
століття. Розглядаються питання його закриття, пристосування під господарські
потреби та руйнування під час Другої світової війни. В статье речь идет о Черниговском Борисоглебском соборе в 20-30-е годы XX века.
Рассматриваются вопросы его закрытия, приспособление под хозяйственные нужды
и разрушения во время Второй мировой войны. The period of 20-30 years of XX century was marked by negative trends regarding
church leaders across the Soviet Union. Ukraine, understandably, was not an exception
in this regard. Anti-religious policy of the Soviet authorities against the members of the
church, of course, carried with them a negative attitude to religious buildings.